KRITERIA KEPENATUAAN MENURUT 1 TIMOTIUS 3:1-7 DAN RELEVANSINYA DENGAN PELAYANAN MASA KINI DI GEREJA SANTAPAN ROHANI INDONESIA - Rusmanto, Ayub (EKKLESIA: Jurnal Teologi dan Pendidikan Kristiani, 2025)
Abstract: The dynamics of church ministry today show the phenomenon of the younger generation not being interested in becoming elders, due to the many rules and requirements. In this case, the researcher examines the criteria for eldership according to 1 Timothy 3: 1-7 and the relevance of the criteria to today's ministry which is still based on Biblical values. Researchers used an investigative descriptive qualitative approach to find understanding and meaning of views or perspectives on the criteria for proper eldership in the midst of Independent Congregations and in the Indonesian Spiritual Sustenance Church Synod and the relevance of the criteria for today's ministry. The purpose of this research is to examine the criteria for eldership according to the text of 1 Timothy 3: 1-7. Because elders and church officials are representations that are exemplified in proportion to the Biblical criteria mentioned by Paul according to the context of the church in Ephesus but are still relevant for the church today. In addition, this research provides findings or novelty, decisions and policies that have an impact on the ministry in the midst of the Indonesian Spiritual Feeding Church congregation that are relevant in today's ministry. Abstrak: Dinamika pelayanan gereja saat ini menunjukkan fenomena generasi muda tidak tertarik untuk menjadi penatua, didisebabkan banyaknya aturan dan persyaratan. Dalam hal ini peneliti menelaah kriteria kepenatuaan menurut 1 Timotius 3:1-7 dan relevansi kriteria dengan pelayanan masa kini yang tetap berlandaskan nilai-nilai Alkitabiah. Peneliti menggunakan pendekatan kualitatif deskriptif investigasi untuk menemukan pemahaman dan pemaknaan pandangan atau perspektif tentang krietria penatua yang tepat di tengah-tengah Jemaat Mandiri dan di Sinode Gereja Santapan Rohani Indonesia dan relevansi kriteria pelayanan masa kini. Tujuan penelitian ini mengkaji kriteria kepenatuaan menurut teks 1 Timotius 3:1-7. Sebab penatua dan pejabat gereja merupakan representasi yang diteladani secara proporsional dengan kriteria Alkitbiah yang disebutkan oleh Paulus sesuai dengan konteks jemaat di Efesus namun masih relevan untuk jemaat masa kini. Selain itu, penelitian ini memberikan temuan-temuan atau kebaruan, keputusan-keputusan dan kebijakan-kebijakan yang berdampak bagi pelayanan di tengah-tengah Jemaat Gereja Santapan Rohani Indonesia yang relevan dalam pelayanan masa kini.